THE EFFECT OF STORYTELLING TOWARDS STUDENTS' SPEAKING SKILL AT X GRADE STUDENTS OF MA NURUL HARAMAIN BOARDING SCHOOL - Yunita Hidayati (Universitas Pendidikan Mandalika, 2019)
This study was aimed to investigate whether or not the use of storytelling has positive effect towards the students' speaking skills at the tenth-grade students of MA Nurul Haramain. The form of this research was pre-experimental study with comparing the scores in pre-test and post-test. The population of this research is the tenth-grade students of MA Nurul Haramain Narmada, with the sample is class X B that consists of 21 students. The research findings show that the mean score of the pre-test is 59.05 and the mean score of post-test is 78.48. It shows that storytelling has a significant impact towards the students' speaking skill. The result of sig. 2-tailed (0.00) is lower than sig. level (0.05), also the result of the t-test is higher than t-table, the value is 4.1 >1.6 it means that the alternative hypothesis (Ha) is accepted. It can be concluded that there is a highly significant effect of storytelling technique towards students' speaking skill on the tenth-grade students of MA Nurul Haramain.